1998
DOI: 10.1007/s004280050226
|View full text |Cite
|
Sign up to set email alerts
|

Biological and prognostic significance of stratified epithelial cytokeratins in infiltrating ductal breast carcinomas

Abstract: The biological significance of the differential expression of cytokeratin (CK) polypeptides in breast carcinomas is unclear. We examined the CK profiles of 101 primary infiltrating ductal breast carcinomas using monoclonal antibodies directed against 11 different CKs and against vimentin. Two major CK phenotypes were distinguished: first, a phenotype expressing only the simple-epithelial CKs 7 (variably), 8, 18 and 19, and secondly, a bimodal phenotype co-expressing significant amounts of one or more of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
144
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 42 publications
16
144
1
3
Order By: Relevance
“…Our finding that some cancer-derived myoepithelial cells are functionally defective, as characterized by a lack of laminin-1 expression and their inability to polarize luminal epithelial cells, provides a plausible explanation for why breast carcinomas showing partial myoepithelial differentiation do not confer a better prognosis for the patients (68). Accordingly, in some breast carcinomas, neoplastic myoepithelial cells are present and appear to be functional.…”
Section: Myoepithelial Cells In Neoplasiamentioning
confidence: 79%
“…Our finding that some cancer-derived myoepithelial cells are functionally defective, as characterized by a lack of laminin-1 expression and their inability to polarize luminal epithelial cells, provides a plausible explanation for why breast carcinomas showing partial myoepithelial differentiation do not confer a better prognosis for the patients (68). Accordingly, in some breast carcinomas, neoplastic myoepithelial cells are present and appear to be functional.…”
Section: Myoepithelial Cells In Neoplasiamentioning
confidence: 79%
“…Likewise, Abd El-Rehim et al 6 reported that tumors expressing basal/myoepithelial phenotype were often ER negative. 7 Seshadri et al 20 convincingly showed that vimentin expression was significantly associated with the absence of hormone receptors. This was comparable to the results reported by Santini et al 21 and Korsching et al 22 The in vitro work in the current study also substantiates the finding that expression of vimentin is correlated with the hormonal status as ERÀ/PRÀ MDA-MB-231 breast cancer cells had significantly higher expression of vimentin than ER þ /PR þ MCF-7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 Various studies carried out previously have evaluated the expression of these cytokeratins and vimentin in human breast cancer. 1,[4][5][6][7] In this paper, we specifically examined the expression patterns of the basal cytokeratins CK5/6, CK14, 34bE12 (CK 1/5/ 10/14), and of vimentin in breast cancers in young women, defined as those aged 35 years or less, and correlated the findings with conventional pathological parameters. Cell Culture MCF-7 and MDA-MB-231 breast cancer cells purchased from the American Type Culture Collection were cultured in Dulbecco's Modified Eagle's Medium (Sigma) supplemented with 10% fetal bovine serum (FBS) and RPMI-1640 with 10% FBS respectively at 371C in a 5% carbon dioxide incubator.…”
mentioning
confidence: 99%
“…Tumor cell expression of p63 indicates acquisition of basal-like attributes, and expression of other basal markers, including cytokeratin 5 and cytokeratin 14, correlate with a more invasive phenotype. 57,58 Recently, it was shown that basal epithelial genes CK14 and p63 are required for collective invasion of breast tumor cells in three-dimensional cultures. 46 Further, the predominant p63 isoform, dNp63a, can function as an oncogene in epithelial cells.…”
Section: Myoepithelium In Dcis Progressionmentioning
confidence: 99%